METODE DEMONSTRASI DALAM PENINGKATAN PEMBELAJARAN FIQIH DI MTsN 14 HULU SUNGAI TENGAH - Ubaidillah Ubaidillah (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
The purpose of this study was to determine the effectiveness of the demonstration method in class VII fiqh subjects at MTsN 14 Hulu Sungai Tengah, what efforts were made to increase the effectiveness of the demonstration method in class VII fiqh subjects at MTsN 14 Hulu Sungai Tengah, what factors became supporters and obstacles in the implementation of the demonstration method in fiqh class VII at MTsN 14 Hulu Sungai Tengah. The type of research used is qualitative research. Sources of data in the study were the Principal of Schools, Fiqh Teachers and Students. The research instruments used were observation guidelines, interview guidelines, and documentation. The data analysis techniques used were data reduction, data presentation, and data verification. The results of the research can be summarized as follows: 1) The use of the demonstration method carried out on class VII MTsN 14 Hulu Sungai Tengah students is very effective because students can directly after explaining the aims and objectives of students can immediately watch the fiqh teacher to give examples to students so that students can watch directly then the students also participate in practicing these activities such as tayamum, ablution and prayer. 2) The efforts made are: the first step to explain in advance the intent and purpose of using the demonstration method in accordance with the material being taught. Prepare students so that they can focus more on the material to be taught. There is discussion or sharing after the use of demonstration methods with students. 3) the factors that become supporters and obstacles, namely: the supporting factors are able to make teaching clearer and more concrete, can stimulate students to be more active in participating in teaching and learning activities, students find it easier to understand what is learned precisely and clearly, can increase Students experience, the teaching process is more interesting, can reduce misunderstanding because teaching is concrete, students are designed to actively observe, adjust theory to reality and try to do it themselves. The second factor is obstacles, these factors can come from students, teachers, facilities, infrastructure, limited time and so on.